Family intervention for the treatment and rehabilitation of drug addiction: an exploratory study - Baharudin, DF; Hussin, AHM; Sumari, M; Mohamed, S; Zakaria, MZ; Sawai, RP (Informa Healthcare, 2024)
Indexed by WOS/ Scopus